Mengetahui Dinamika Budaya Di Tempat Kerja Yang Berkorelasi Dengan Interaksi Budaya Dalam Organisasi Yang Mempengaruhi Kenyamanan Lingkungan Kerja Serta Produktivitas Kerja Meninjau Dari Perspektif Fisik Dan Sosial - Sarah Fauziah Saefudin; Serani Arta Mauli Silalahi2 (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
Activities that take place in an office environment are closely related to the role of a company's human resources (HR) department. Human resource management is very important in efforts to increase organizational effectiveness and productivity. One aspect that needs to be considered is how an employee's social culture affects their performance and their relationship with employees as well as their overall work productivity. The literature review approach is the author's method of researching relevant secondary data to support the claims made in this article. Collected research shows that cultural interactions between employee habits have a significant impact on individual and team performance as a whole. This includes various physical and social aspects, therefore it is important to know and be aware of the importance of this. The results of the survey also revealed that the majority of respondents, even 70%, admitted that their relationships with co-workers had a significant influence on work life satisfaction and happiness. The influence of these social habits affects the productivity and comfort of employees' office environments. Where this will provide an increase or decrease in employee performance. Therefore, we hope that this article can be a useful resource for various companies to understand the importance of the impact of employee habits on a pleasant work atmosphere and overall employee productivity. Realizing this will hopefully lead to more proactive strategic steps in creating a work environment that supports individual and team development and increases overall efficiency and productivity. The theme raised in the title of the article is